TEORI DAN MODEL PENGUKURAN KEPUASAN MASYARAKAT TERHADAP KEBERKESANAN SISTEM PELAYANAN PUBLIK - Embi, Muhamad Ali; Widyasari, Rita (TINGKAP, 2013)
The success of service delivery system can be measured by the level of services satisfaction according to community needed and expected. Standards of services delivery is a benchmark used to assess the quality of services delivery as a commitment or a promises from the service provider to the user to provide a quality services. While quality service is prompt, pleasant, does not contains errors, and follow the process and procedures in advance. Therefore, the quality of services does not only determined by the service provider but also the user of the service. Accordingly, this article will discuss theories related to public service and community satisfaction measurement models. Keywords: public service, Â qualified service, citizenship satisfaction